Test bench for fibers of the LHAASO-WCDA time calibration system. (26th October 2017) - Liu, J.Y.; Gao, B.; Yu, C.X.; Chen, M.J.; Luo, Y.A.; Yao, Z.G.; Zha, M.; Wu, H.R.; Li, H.C.; Wang, X.J.
Abstract: The Water Cherenkov Detector Array (WCDA), which is one of the main components of the Large High Altitude Air Shower Observatory (LHAASO), functions in surveying the northern sky for high-energy gamma ray sources at the energy range around of 100 GeV–30 TeV. The precision of the time measurement for shower particles hitting every detector in the array is directly associated with the detection sensitivity for the sources. The calibration precision of the time offsets among the detector cells should be less than 0.1 ns to obtain less than0.1^° 0.1 ̂ pointing error of the detector to any point source. In this regard, "cross calibration" is employed for the detector array, with 180 bundles of fiber systems guiding the lights of LEDs to each PMT. A test bench comprising fast PMTs and an one-dimensional slide platform is set up in the laboratory to test the fiber bundles. The test bench and the test procedure is described in this paper, and the test results are presented.